FOXA1-dependent NSUN2 facilitates the advancement of prostate cancer by preserving TRIM28 mRNA stability in a m5C-dependent manner - Zhenda Wang; Abudurexiti Mierxiati; Wenkai Zhu; Tian Li; Hua Xu; Fangning Wan; Dingwei Ye (npj Precision Oncology)
Abstract RNA epigenetics is gaining increased attention for its role in the initiation, metastasis, and drug resistance of tumors. These studies have primarily focused on m6A modification. However, despite being the second most abundant modification found in RNA, the role of m5C modification in prostate cancer remains largely unexplored. Here, we predict an RNA m5C methyltransferase, NSUN2, as a potential therapeutic target for prostate cancer using various bioinformatics approaches, and verify the potential of NSUN2 as a target through multiple preclinical models. Mechanistically, NSUN2 enhances the stability of TRIM28 mRNA by adding m5C modification, promoting the expression of TRIM28. Concurrently, FOXA1, a prostate cancer lineage-specific transcription factor, transcriptionally activates the expression of NSUN2. Our study confirms the clinical potential of targeting RNA epigenetics for the treatment of prostate cancer and elucidates, mechanistically, how RNA epigenetics participates in the complex biological activities within tumors via the FOXA1-NSUN2-TRIM28 axis.